Molecular dynamics simulations of protein dynamics, unfolding and misfolding - Daggett, Valerie (Henry Stewart Talks, 2007)
Molecular mechanics force fields and starting structures, Molecular dynamics (MD) simulations, Native protein dynamics, Protein unfolding, Unfolding pathways of En-HD, Protein unfolding and disease, Objectives for MD simulations